Project Based Learning Assisted by Peer Assessment to Promote the Students’ Critical Thinking Ability in The Tertiary Level of Education - Djunaidi, Djunaidi; Jaya, Aswadi (Yayasan Sembilan Pemuda Indonesia, 2024)
The objective of this study was to analyze the effect of learning project-based learning assisted by peer assessment in hybrid learning to improve students’ critical thinking skills as the implementation of literacy practices. The study uses the posttest only control group design. The population of this study was all second semester English Education Study Program students in PGRI University of Palembang, totaling 170 students. Descriptive statistical analysis techniques are used to describe the data obtained. The hypothesis testing used is the t-test to test the significant level of the influence of the independent variables partially on the dependent variable. The test is carried out by comparing t-count with t-table. The results of the analysis show that the value of Sig. obtained less than 0.05. This means that there are differences in students’ critical thinking skills being taught project-based learning (PJBL) assisted by peers with students who are taught without learning project-based learning (PJBL) assisted by peers. The implications of this research goes that it is hoped that with this learning model students will learn more actively in building their own knowledge as the literacy processes which will have an impact on critical thinking skills.